Polycaprolactone nanofibers functionalized with a dopamine coating for on-line solid phase extraction of bisphenols, betablockers, nonsteroidal drugs, and phenolic acids - Háková, Martina; Havlíková, Lucie Chocholoušová; Chvojka, Jiří; Erben, Jakub; Solich, Petr; Švec, František; Šatínský, Dalibor (Mikrochimica acta, 2019)
Polycaprolactone composite nanofibers coated with a polydopamine layer are introduced as a new type of absorption material for on-line solid phase extraction (SPE) in chromatographic system. A hybrid technology combining the electrospinning and melt blowing was used for the preparation of 3D-structured microfiber/nanofibrous polycaprolactone composite. The dopamine coating was then applied to functionalize the micro/nanofibers. Polydopamine-coated polycaprolactone fibers were tested as an extraction phase in on-line SPE prior to HPLC separation and UV detection. Four groups of biologically active substances including bisphenols (Bisphenol S, Bisphenol AF, Bisphenol A, Bisphenol C, Bisphenol AP, Bisphenol Z, Bisphenol BP, and Bisphenol M), betablockers (Timolol, Metoprolol, Labetalol, and Propranolol), nonsteroidal antiphlogistic drugs (Salicylic acid, Ketoprofen, Naproxen, Indomethacin, Diclofenac, Ibuprophen, and Meclofenamic acid), and phenolic acids (Chlorogenic acid, Caffeic acid, Sinapic acid, m-Coumaric acid, Benzoic acid, and Cinnamic acid) were used as the model analytes. Neat and coated fibers were compared and applied as sorbents for the on-line extraction set-up. Both materials produced good extraction potential for the determination of bisphenols and nonsteroidal drugs in model biological and environmental samples including river water, human urine, and blood serum. However, the polydopamine layer significantly increased the extraction efficiency of polar drugs. Typical repeatability of on-line extraction procedure on polydopamine coated fibers was in the range 0.12-4.11% for bisphenols, 0.55-1.41% for antiphlogistic drugs, 0.59-2.52% for phenolic acids, and 1.01-1.65% for betablockers. Graphical abstract Schematic representation of polycaprolactone composite nanofibers coated with a polydopamine layer as an advanced absorption material for on-line solid phase extraction in chromatography.
Keywords: Cinnamates; nanovlákna; Adrenergic beta-Antagonists; Polymers; Anti-Inflammatory Agents, Non-Steroidal; Nanofibers; vysokoúčinná kapalinová chromatografie; Indoles; řeky; polyestery; Polyesters; Polymerization; chemické látky znečišťující vodu; extrakce na pevné fázi; cinnamáty; antiflogistika nesteroidní; polymerizace; Chromatography, High Pressure Liquid; Phenols; Reproducibility of Results; Rivers; reprodukovatelnost výsledků; beta blokátory; fenoly; indoly; Solid Phase Extraction; Water Pollutants, Chemical; polymery